2007
DOI: 10.1097/01.brs.0000255023.56466.44
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Randomized Study of Unilateral Versus Bilateral Instrumented Posterolateral Lumbar Fusion in Degenerative Spondylolisthesis

Abstract: Unilateral instrumentation used for the treatment of degenerative lumbar spondylolisthesis is as effective as bilateral instrumentation when performed in addition to 1- or 2-level posterolateral fusion. The cost of this method is lower, saves time, and reduces possible risk inserting screws in only one side.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
75
1
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 94 publications
(80 citation statements)
references
References 44 publications
3
75
1
1
Order By: Relevance
“…Several randomised controlled clinical trials have shown that there is no clinical benefit from bilateral over unilateral instrumentation in posterolateral fusion alone. The main benefits of unilateral fixation seem to be less blood loss and muscle dissection, shorter operative time and hospital stay, lower medical cost, and fewer complications related to implants [12,20,21,24]. These results were also observed in our study.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…Several randomised controlled clinical trials have shown that there is no clinical benefit from bilateral over unilateral instrumentation in posterolateral fusion alone. The main benefits of unilateral fixation seem to be less blood loss and muscle dissection, shorter operative time and hospital stay, lower medical cost, and fewer complications related to implants [12,20,21,24]. These results were also observed in our study.…”
Section: Discussionsupporting
confidence: 80%
“…Lumbar interbody fusion can reach almost 100 % fusions, whereas the fusion rate of posterolateral arthrodesis with unilateral fusion ranges between 90 % and 97 %, especially with a lower rate in two-level fusion [11][12][13]25]. In this study, we found that the fusion rate of two-level fusion in the unilateral fixation group was similar to that in the bilateral fixation group (90.91 % vs 94.29 %).…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations